Porównanie przebiegu temperatury powietrza i wilgotności względnej w Petuniabukta i Svalbard-Lufthavn (Spitsbergen) w sezonie letnim 2016 - Kendzierski, Sebastian (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2017)
This work presents the values of air temperature and relative humidity measured in the period 7th July 2016 – 31th August 2016 in Petuniabukta and Svalbard-Lufthavn. The course of air temperature and humidity was compared. These values depend primarily on the type of atmospheric circulation. In the article, basic statistical methods were used (arithmetic mean, standard deviation, correlation Pearson coefficient). The research revealed that Petuniabukta point is colder by 0.2°C and has higher average relative humidity of about 3%. Higher temperatures cause smaller differences of air temperature and relative humidity at the tested points. Also in this case, a lower value for relative humidity was observed.
Keywords: Svalbard; Spitsbergen; Petuniabukta; Svalbard-Lufthavn; Arctic, air temperature; relative humidity